The establishment of the Chinese legation in Tehran: Chungking’s Middle Eastern strategies and the British Foreign Office (1941-1942) - Miele, Matteo (Thai Journal of East Asian Studies, 2021)
In 1942 the Republic of China established a legation in Tehran. Neither during the last years of the Qājār dynasty nor during the subsequent reign of Reẕā Pahlavī did the Chinese manage to send a diplomatic mission to the capital of the Empire. The change in attitude by the Persian government must therefore obviously be attributed to the new international role of Iran after the Anglo-Soviet invasion of 1941, the abdication of Reẕā Pahlavī, and the accession to the throne of his son Moḩammad Reẕā Pahlavī. Furthermore, the Republic of China, engaged in the hard and long conflict with Japan, was trying to build a diplomatic network in the Near and Middle East that would also support the international re-legitimation after the humiliations suffered since the First Opium War. In particular, the opening of the legation meant the full implementation of the Sino-Persian treaty of 1920. After more than twenty years, the political meaning of that document was probably reconsidered in light of the negotiations with the United States and the United Kingdom regarding extraterritorial rights. The paper, therefore, outlines the political issues and objectives around the opening of the Chinese legation, trying to analyze the role played by the Foreign Office and the British legation in Tehran.